Detection of RNA-protein interactions using a highly sensitive non-radioactive electrophoretic mobility shift assay - Daras, G.; Alatzas, A.; Tsitsekian, D.; Templalexis, D.; Rigas, S.; Hatzopoulos, P.
Electrophoretic mobility shift assay (EMSA)is a sensitive technique useful in the identification and characterization of protein interactors with nucleic acids. This assay provides an efficient method to study DNA or RNA binding proteins and to identify nucleic acid substrates. The specific interaction plays important roles in many biological processes such as transcription, translation, splicing, and global gene expression. In this article, we have modified the EMSA technique and developed a non-radioactive straightforward method to study and determine RNA-protein interactions. The labeling of target RNAs by 3'-end biotinylation and the detection of biotin reactivity to streptavidin-conjugated horseradish peroxidase is a highly sensitive approach capable to detect the formation of RNA-protein complexes. Overall, we provide a complete technical guide useful to determine in vitro RNA-protein interactions and analyze RNA target specificity.
Keywords: EMSA; GEL RETARDATION; GEL SHIFT; RNA; RNA-PROTEIN INTERACTIONS